Cardiolipin’s multifaceted role in immune response: a focus on interacting proteins - Chai, Zhuodong; Zhou, Yuqi; Hossain, Sukria; Huynh, Khanh; Hajimirzaei, Sahelosadat; Zhang, Yan; Qi, Jiaqian; Zhang, Guoying; Li, Zhenyu; Wei, Yinan (Frontiers in Immunology, 2025)
Cardiolipin is a unique and essential phospholipid that plays a pivotal role in cellular function. In eukaryotic cells, it is predominantly localized within the mitochondrial membranes, with the highest concentration in the inner mitochondrial membrane (IMM). Recent studies have highlighted the multifaceted role of cardiolipin in immune regulation. This review aims to provide a comprehensive overview of specific proteins that directly interact with cardiolipin and to elucidate how these interactions underlie its diverse and critical functions in innate immunity. In addition, we discuss the involvement of cardiolipin in various pathological conditions in which its protein interactions contribute to immune dysregulation.